"Where Them Bloggers At?": Reflections on Rihanna, Accountability, and Survivor Subjectivity - Bierria, Alisa (Social justice, 2010)
This article discusses the public and media responses to the assault of Barbadian singer Rihanna by her boyfriend, American rapper Chris Brown. Topics include ways that online sources collectively called for Rihanna's accountability and the difficulty of African American women to occupy the role of victim in domestic assault cases, a discussion of domestic violence in the hip-hop community, and ways that racialized sexism drove the discussion even among traditionally feminist blogs and online communities, particularly with regards to Afro-Caribbean women.